Effect of neem cake in the management of root knot nematode: Effect of neem cake in the management of root knot nematode - DEEPA S P; SANKARI MEENA K (Journal of Oilseeds Research, 2023)
Neem enrichment extract (NEE) was used at different concentrations viz., 0, 2.5, 5 and 10% to check its effect on second stage juveniles of Meloidogyne spp. Root knot nematode bio-assay in Petri Plates as well as in pot culture experiments were carried out with NEE.The results indicated that neem cake extracts was effective to control the root knot nematodes due to the presence of biological substance (azadirachtin, salannin, nimbin) and its derivative compounds (triterpenoid, limonoid).